A Tentative Mechanism of Solubilization of Neuropathy Target Esterase from Chicken Embryo Brain by Phospholipase A2 - Josef Seifert (The Scientific World Journal)
The neuropathy target esterase is a membrane-bound enzyme linked to organophosphate-induced distal neuropathy. Here we report a tentative mechanism of its solubilization from chicken embryo brains by using phospholipase A2. The enzyme was released from brain membranes after degradation of their structural phospholipids initiated by phospholipase A2. L-α-lysophosphatidylcholine, tested as a representative product of phospholipid hydrolysis, was identified as a new efficient detergent for solubilization of the neuropathy target esterase.